Comparative analysis of six search engines using terms taken from macrothesaurus for information processing in the field of economics and social development - Mayor, Jansen M. (1999)
The growing popularity of Internet as a source of information has fueled the growth of search engines. Search engines are facilities that help users find information through the vast reservoir of knowledge that can be found on the Internet. This study is an evaluation of the performance of the six popular search engines.